Digitalization of Islamic Philanthropy: Transparency and Accountability of Zakat and Waqf Crowdfunding Platforms - Muhammad Firdaus; Taofeek Muhammed Thani; Ismail Jalili; M. Anzaikhan (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2026)
Purpose: This study aims to analyze the digitalization of Islamic philanthropy through zakat and waqf fundraising platforms and assess its compliance with the principles of transparency (al-syafāfiyyah) and accountability (mas’ūliyyah) within the framework of Islamic economic law and maqāṣid al-sharī‘ah.Design/Methodology: This study employs a qualitative library research design with a juridical-normative approach. It employs a conceptual and legal approach by examining primary sources, including the Quran, Hadith, fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and related regulations, as well as secondary sources such as academic literature and previous research related to Islamic philanthropy and crowdfunding practices.Findings: The findings indicate that the digitalization of Islamic philanthropy through crowdfunding platforms is permissible under Islamic law, provided it meets essential sharia requirements, including clear contractual arrangements (akad), transparent information disclosure, accountability for fund distribution, and effective sharia oversight. However, challenges remain regarding standardized reporting mechanisms, oversight models, and the alignment of digital practices with the principles of trustworthiness and justice (‘adl). Adherence to these principles ensures the realization of benefits to society (maslahah) and the maintenance of the community's trust.Practical Implications: This study highlights the importance of strengthening the regulatory framework, enhancing sharia governance, and developing standardized transparency and accountability mechanisms for zakat and waqf fundraising platforms. These measures support sustainable digital philanthropy and strengthen public trust in Islamic social financial institutions.Originality/Value: This study provides a normative legal analysis of digital zakat and waqf fundraising platforms from the perspective of Islamic economic law, offering a structured evaluation framework based on the principles of transparency, accountability, and maqāṣid al-sharī‘ah in the digital era